Analysis of ICT Energy Efficiency Disclosure to Improve Business Management Practices and Its Contribution to the SDGs - Manuela Sánchez-Vázquez; Ainhoa Saitua-Iribar; Noemí Peña-Miguel; Javier Corral-Lage (Administrative Sciences)
Purpose: The new global approach to sustainability within the context of the SDGs is driving a digital transition. However, new technologies bring challenges related to the energy efficiency of their infrastructures. The aim of this exploratory work is to identify the companies with best practices in various aspects of the management, disclosure and verification of the energy efficiency of emerging technologies. Design/methodology/approach: Using a mixed qualitative and quantitative approach, the Non-Financial Information Statements of Spanish IBEX 35 companies are assessed. Findings: The results show that companies disclose non-financial information in relation to the materiality of energy efficiency and the actions implemented to improve it, but regulatory development is still required to ensure greater comparability of such information. Originality: To the best of our knowledge, this is the first study to analyse information on ICT energy sustainability in the context of Law 11/2008 in Spain, which also includes an analysis of information on the double materiality of risks and the policies and actions implemented by companies to manage them. Practical implications: Improving the information disclosed will increase its usefulness for the internal decision-making of companies, to improve ICT energy efficiency and SDG. Social implications: Improving the information disclosed will increase its usefulness for external decision-making by the different stakeholders, as regulators and other disclosing companies may take these selected companies as an example in each sector of activity.